The Greek Tragedy in the Health Sector: Social and Health Implications - Platon Yvantopoulos; John Yvantopoulos (Vierteljahrshefte zur Wirtschaftsforschung, 2015)
Greece went into recession in 2009, after a decade of flourishing economic growth fluctuating annually around 4 percent; over the same period the average growth for the Eu-27 was just about 2 percent. The economic downturn had a series of adverse effects on the economy and the health sector. More specifically, over the 2008-2015 period, GDP was reduced by 29.5 percent, wages were reduced by 35-45 percent, private consumption dropped by 30 percent and health expenditure declined by 41 percent. At the same time income inequality (shares S80/S20) increased by 11 percent and the unemployment rate reached 27.1 percent (an increase of 276.4 percent). The share of population at risk of poverty increased from 27.6 percent in 2009 to 36 percent in 2014. While life expectancy stabilized at about 80 years, infant mortality increased from 2.7 in 2008 to 3.8 in 2010, with a subsequent marginal reduction. The Eurozone countries and the IMF provided three rescue packages to Greece. The first economic adjustment program was signed in May 2010 between Greece and Troika (the European Commission, The European Central and the IMF) was worth 110 billion euro. The second adjustment program was signed in February 2012 and worth 130 billion euro, while the third one in June 2015 amounted to 86 billion euro. The terms of these bailouts included a series of required reforms, such as the liberalization of several protected economic and employment sectors, the reduction of public expenditures, the fight against corruption and the underground economy, the control of health expenditures, and the implementation of an austerity package. Consequently, the economic crisis has brought a significant deterioration to the health status and quality of life of the Greek Population. A set of quality of life instruments is used to assess the impact of the crisis on a Visual Analogue Scale (VAS). The quality of life mean scores indicated a significant deterioration of subjective health by 10 points. The VAS before the crisis was VASBefore= 86.06 (st.d. =15.14) and the corresponding value during the crisis was VAS During = 76.72 (st.d. = 20.51). The significant reduction in VAS was also associated with greater inequalities in the distribution of health. In addition low-income individuals declared losses of jobs, fears of long unemployment, and a significant deterioration of their psychological and emotional status. The findings will help develop better targeted health policies that seek to improvement of the health of the Greek population.
Keywords: G01; G28; I10; L88; 330; Austerity; economic crisis; health expenditure; health sector; Greece